TEMPERATURE OPTIMIZATION AGAINST P-METHOXYCINAMIC ACID SYNTHESIS THROUGH ULTRASONIC WAVE-ASSISTED KNOEVENAGEL CONDENSATION - Indriyanti, E.; Suryaning P, M.; Purwaningsih, Y.; Sulistiyanto, F. X. (Jurnal Kimia (Journal of Chemistry), 2022)
Cinnamic acid derivative compounds are found in almost all plants but the quantity is very small that it cannot only rely on the results collected from the extraction method or the isolation of plant parts alone. Increasing amount of production of cinnamic acid derivatives can be done by chemical synthesis. One of the cinnamic acid derivatives that can be synthesized is p -methoxycinamic acid. It is a derivative of cinnamic acid that is substituted by a methoxy group at para position. The synthesis of this cinnamic derivative was obtained through the knoevenagel condensation reaction with the sonochemical method by reacting 6.61 mmol anisaldehyde, 16.8 mmol malonic acid, and 1.12 mmol ?-alanine dissolved in 37.1 mmol pyridine in an Erlenmeyer flask, then sonicated for 60 minutes at temperatures (40 0 C, 50 0 C, 60 0 C). The synthesized compound was tested organoleptically and its melting point was measured. The result structure was elucidated using FTIR and GC-MS. The synthesized compound in the form of shiny white fine crystals had a distinctive odor and an optimum temperature of 60 0 C and produces % yield of 92.71%. The results of the structural elucidation test of the synthesized compound using FTIR-ATR showed the presence of an OH carboxylate group, C=O carboxylate, C=C, an aromatic group, C=C conjugated aromatic group, and aromatic substitution in the para position. Testing by GC-MS found that the compound has a purity of 100% with a retention time of 11.71 minutes, with a base peak of 178 m/z with a relative abundance of 100%. Keywords : elucidation, knoevenagel, p -methoxycinamic acid, synthesis, sonochemical.                Senyawa-senyawa turunan asam sinamat terdapat hampir di semua tanaman namun kuantitasnya sangat kecil sehingga tidak bisa hanya mengandalkan hasil-hasil yang dikumpulkan dari metode ekstraksi ataupun isolasi bagian tanaman saja. Peningkatan jumlah produksi dari senyawa-senyawa turunan asam sinamat dapat dilakukan dengan sintesis kimia. Salah satu turunan asam sinamat yang dapat disintesis adalah asam p- metoksisinamat. Senyawa asam p- metoksisinamat merupakan senyawa turunan dari asam sinamat yang tersubstitusi gugus metoksi pada posisi para. Sintesis turunan sinamat ini didapatkan melalui reaksi kondensasi knoevenagel dengan metode sonokimia dengan mereaksikan 6,61 mmol anisaldehid, asam malonat 16,8 mmol, dan ?-alanine 1,12 mmol dilarutkan dalam piridin 37,1 mmol dalam labu Erlenmeyer, kemudian disonikasi selama 60 menit pada suhu (40 0 C, 50 0 C, 60 0 C ). Senyawa hasil sintesis diuji organoleptis dan diukur titik leburnya. Struktur hasil dielusidasi menggunakan  FT-IR dan GC-MS. Senyawa hasil sintesis berupa Kristal halus berwarna putih mengkilap memiliki bau khas dan  suhu optimum 60 o C dan menghasilkan % yield sebesar 92,71%. Hasil Uji elusidasi struktur menggunakan FTIR-ATR dari senyawa hasil sintesis menunjukkan adanya gugus  OH karboksilat, C=O karboksilat, C=C, gugus aromatik, C=C terkonjugasi gugus aromatik, dan substitusi aromatik di posisi para. Pengujian dengan GC-MS didapatkan senyawa memiliki kemurnian 100% dengan waktu retensi 11,71 menit, dengan base peak 178 m/z dengan kelimpahan relatif 100%. Kata kunci : asam p- metoksisinamat, elusidasi, knoevenagel, sintesis, sonokimia.